Latin american youth identity, based on the analysis of the impact of glocal socio-communicative discourse. Colombia case [Identidad juvenil latinoamericana a travÉs del anÁlisis de los discursos sociocomunicativos glocales. Caso colombia] (2021)
This article is the result of the research project which inquired about the existence of a common Latin American Youth Identity, based on the analysis of the iconic references of young people. The methodology, which was shared with researchers from Spain and Argentina, incorporated participatory tools in a research seedbed with communication students from the University of Medellin. The analysis was based on Panofsky´s principles of iconology (1998), through techniques of collaborative/cooperative work. The main findings point to the historical and institutional mediation in the conformation of the Youth Identity, configured from the social discourses. © 2020 Universidad de Alicante. All rights reserved.